ROLE OF HYPOXIA-INDUCIBLE FACTOR 1A (HIF1A) ON INTERMITTENT HYPOXIAINDUCED ADIPOSE TISSUE DYSFUNCTION IN TYPE 2 DIABETES MELLITUS - Poblete, Josept Mari; Bao, Shengying; Nevado Jr., Jose; Magalang, Ulysses (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Obstructive sleep apnea (OSA) commonly coexists in type 2 diabetes mellitus (T2DM) patients, but the mechanism for this overlapping epidemic remains unclear. We hypothesized that the intermittent hypoxia (IH) in OSA leads to upregulation of hypoxia-inducible factor 1a (HIF1A) in adipose tissue (AT), leading to local fibrosis, inflammation, and macrophage infiltration. These contribute to insulin resistance and glucose intolerance in T2DM. METHODOLOGY We employed a combination of in vitro and in vivo approaches to investigate the role of HIF1A in OSA and T2DM. Cell and animal models were exposed to IH to simulate the hypoxic stress in OSA. The role of HIF1A was investigated through treatment with PX-478, a known HIF1A inhibitor. RESULTS IH exposure resulted in IL6-mediated inflammation in adipocytes and macrophage co-culture that was reversed by pre-treatment with PX-478. Further, TallyHo mice treated with PX-478 had markedly improved insulin sensitivity and glucose tolerance after IH challenge. These metabolic improvements were associated with decreased AT fibrosis, inflammation and macrophage infiltration. Trichrome stain indicated that collagen deposition was significantly reduced in AT of PX-478-treated TallyHo mice exposed to IH. We also found that the inflammatory markers IL6, TNFa and MCP1 were decreased in AT of PX-478-treated mice. Consistent with these, immunohistochemical staining confirmed lower frequency of macrophage infiltration in the PX-478 group. CONCLUSION Overall, we underscore the importance of HIF1A for the orchestration of pro-fibrotic and pro-inflammatory changes of the AT in response to IH, serving as a crucial link between OSA and the development of insulin resistance and glucose intolerance in T2DM.